REDESIGN STRUKTUR ATAS BANGUNAN CELLA CAKUNG LOGISTIC WAREHOUSE - Fruisttha Aulia Cahyani; Tri Widya Swastika (Politeknik Negeri Jakarta, 2026)
Efficient and code-compliant steel structural design is essential in the development of industrial buildings such as logistic warehouses. This study aims to conduct a comparative evaluation of the structural capacity of steel elements between the existing design and an alternative design in logistic warehouse building located in Jakarta, in which the existing structure uses a combination of concrete and steel materials, while the alternative design adopts a fully steel structural system. The analysis focuses on primary structural elements, columns with King Cross profile and beams with Castellated. Structural modelling and analysis were performed using SAP2000, referring to SNI 1729:2020 for steel structure design and SNI 1726:2019 for seismic loading. The alternative design was developed using a preliminary design approach through a trial-and-error method to obtain section dimensions with acceptable capacity ratios (less than 1.0). The comparison parameters include section dimensions, axial and flexural capacities, and element capacity ratios. The results indicate that several elements in the existing structure exhibit capacity ratios exceeding 1.0, whereas the proposed alternative design provides sections that satisfy the required strength criteria. This study limited to the evaluation of primary structural elements and does not include connection design; therefore, the findings are expected to provide an initial reference for selecting more adequate steel sections in similar warehouse structures.